Test Anxiety: A Political Problem, An Alternative View - Carr, Rey A. (Canadian Journal of Counselling and Psychotherapy, 2012)
The conceptual framework expressed by Deffenbacher (1977) in his article "Test Anxiety: The Problem" is challenged and described as being inadequatefor a thorough understanding of test anxiety. The present article describes test anxiety as a political problem needing preventive counselling strategies rather than remedial corrective approaches. Testing and evaluation are seen as tools of oppression and a means to express power and authority in educational settings. By assuming that test anxiety is the student's problem, school counsellors contribute to the problem by facilitating a student's guilt. Counsellors may work to eliminate the problem through consulting with faculty, acting as student advocates, and publicly affirming research findings on humanistic growth.